Novel modular chimeric antigen receptor spacer for T cells derived from signal regulatory protein alpha Ig-like domains - Koski, Jan; Jahan, Farhana; Luostarinen, Annu; Schenkwein, Diana; Ylä-Herttuala, Seppo; Göös, Helka; Monzo, Hector; Ojala, Päivi M.; Maliniemi, Pilvi; Korhonen, Matti (Frontiers in Molecular Medicine, 2022)
Background: T cells equipped with chimeric antigen receptors (CAR) have shown remarkable efficacy in targeting B lineage malignancies. Improvement of the CAR structure is needed, however, with a view to developing flexibly modifiable spacers that are inert in interactions with unwanted cells. Specifically, binding to cells carrying receptors for IgG’s crystallizable fragment (FcR), that recognize IgG-derived domains in CARs is to be avoided. Methods: Two novel CARs targeting the CD19 antigen where the IgG1-CH2 and -CH3 domains were replaced with Ig-like domains from signal-regulatory protein α (SIRPα) were designed in silico. An IgG1-based CAR and a CAR lacking both SIRPα and IgG1 domains were used as comparators. The phenotype and memory phenotype of the expanded cells were analyzed by flow cytometry, and CAR T cell activation and cytotoxic efficacy were assessed in co-culture experiments in response to CD19+ target cells. Unwanted interactions with FcR-expressing myeloid cells were interrogated in co-culture assays with THP-1 monocytic cells. Results: T cells carrying the novel SIRPα-based CARs enacted potent in vitro cytotoxicity against CD19 positive B-lineage leukemia cells, comparable to traditional IgG1-based CAR T cells. Co-culture of IgG1-based CAR T cells with FcR-expressing THP-1 monocytic cells led to prominent cell surface expression of CD69 on T cells together with production of Interleukin (IL)-2 and Interferon-γ, and production of IL-1β, indicating activation of the T cells and monocytes, respectively. Longer co-culture led to killing of the monocytes. No signs of T cell nor monocyte activation were detected in co-cultures of SIRPα-based CAR T cells with THP-1 cells. Arming T cells with the SIRPα-based CARs favored differentiation towards CD4+ phenotype during expansion, while the effects on memory phenotype of the T cells were equivalent between the SIRPα- and IgG1-based CARs. In a pilot experiment, T cells modified with one of the SIRPα-based CARs showed dose dependent leukemia cell control. Conclusion: The novel SIRPα based spacers offer a suitable backbone for developing chimeric antigen receptors that evade the off-target binding to FcR while the cells retain a favorable memory phenotype and efficient cytotoxicity, establishing a promising candidate for future in vivo and clinical testing.